Kitāb al-mabāḥith wal-shukūk : Nukhushtīn taʿlīqa bar al-Ishārāt wal-tanbīhāt, hamrāh bih Kitāb ʿUyūn al-masāʾil-i Fārābī wa Risāla-yi l-Asmāʾ al-mufrada-yi Kindī - Masʿūdī, Sharaf al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
The Kitāb al-ishārāt wal-tanbīhāt of Avicenna (d. 428/1037) is the most influential philosophical compendium in the history of the Islamic world. Being his last major work, written towards the end of his life, the Ishārāt contains what Avicenna considered to be the gist of all there was to know in logic and philosophy. It is different from his other works in that it represents the ultimate stage of development of his philosophical method, transcending the familiar Aristotelian aporetic method of his earlier days, to culminate in an elliptical kind of discourse in which, by the use of pointers or hints, the maximum is asserted with a minimum of means. The commentary by Sharaf al-Dīn Masʿūdī (d. before 605/1208) published here in facsimile is the earliest to survive. Focussing on a limited number of questions, it is not a running commentary. Two other philosophical texts by al-Fārābī (d. 339/950) and al-Kindī (d. after 247/861) accompany it.